Idiopathic Congenital Lymphedema - A Case Report - Baki, Md Abdul; Begum, Suraiya; Haque, Afroza; Begum, Tahmina; Zabeen, Bedowra; Nahar, Nazmun (Bangladesh Journal of Child Health, 2013)
DOI: http://dx.doi.org/10.3329/bjch.v37i1.15352 BANGLADESH J CHILD HEALTH 2013; VOL 37 (1) : 49-51